New Antibacterial Chloro-Containing Polyketides from the Alga-Derived Fungus Asteromyces cruciatus KMM 4696 - Olesya I. Zhuravleva; Galina K. Oleinikova; Alexandr S. Antonov; Natalia N. Kirichuk; Dmitry N. Pelageev; Anton B. Rasin; Alexander S. Menshov; Roman S. Popov; Natalya Yu. Kim; Ekaterina A. Chingizova; Artur R. Chingizov; Olga O. Volchkova; et al. (Journal of Fungi, 2022)
Six new polyketides acrucipentyns A–F (1–6) were isolated from the alga-derived fungus Asteromyces cruciatus KMM 4696. Their structures were established based on spectroscopic methods. The absolute configurations of acrucipentyn A was assigned by the modified Mosher’s method and ROESY data analysis. Acrucipentyns A–E were identified to be the very first examples of chlorine-containing asperpentyn-like compounds. The cytotoxic and antimicrobial activities of the isolated compounds were examined. Acrucipentyns A–F were found as antimicrobial agents, which inhibited sortase A enzyme activity, bacterial growth and biofilm formation of Staphylococcus aureus and decreased LDH release from human keratinocytes HaCaT in S. aureus skin infection in an in vitro model.